2017
DOI: 10.1111/pcmr.12546
|View full text |Cite
|
Sign up to set email alerts
|

Oculocutaneous albinism type 1: link between mutations, tyrosinase conformational stability, and enzymatic activity

Abstract: Summary Oculocutaneous albinism Type 1 (OCA1) is an autosomal recessive disorder caused by mutations in the tyrosinase gene. Two subtypes of OCA1 have been described: severe OCA1A with complete absence of tyrosinase activity and less severe OCA1B with residual tyrosinase activity. Here, we characterize the recombinant human tyrosinase intra-melanosomal domain and mutant variants, which mimic genetic changes in both subtypes of OCA1 patients. Proteins were prepared using site-directed mutagenesis, expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 56 publications
(73 reference statements)
7
68
0
4
Order By: Relevance
“…These observations are consistent with our molecular modeling of human tyrosinase, which suggests that the six sites are located at the protein surface and have less influence on the 4-helix bundle structure maintaining the copper-binding sites (Dolinska et al, 2014, 2017). However, the conformation of the 4-helix bundle in a fully deglycosylated tyrosinase (7D) could be affected by N371D mutation due to an additional negative charge introduced in the protein cavity surrounding this residue.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These observations are consistent with our molecular modeling of human tyrosinase, which suggests that the six sites are located at the protein surface and have less influence on the 4-helix bundle structure maintaining the copper-binding sites (Dolinska et al, 2014, 2017). However, the conformation of the 4-helix bundle in a fully deglycosylated tyrosinase (7D) could be affected by N371D mutation due to an additional negative charge introduced in the protein cavity surrounding this residue.…”
supporting
confidence: 90%
“…In the T373K mutation, which is very common in Northern Europeans, the threonine residue is replaced with positively charged lysine, which disrupts N-X-S/T sequence motif. Results from genetic studies agree with our in vitro data suggesting that T373K mutation causes the proteolytic degradation of expressed protein, destabilization of the tyrosinase structure, and abolishs protein activity (Dolinska et al, 2017). Previously shown in vivo these mutations could prevent tyrosinase from leaving the ER and initiate a severe disease phenotype in OCA1 albinism causing the loss of pigment (Branza-Nichita et al, 2000).…”
supporting
confidence: 89%
“…Although this was reasonable (and standard practice) we generated human full-length tyrosinase and showed that it had similar enzymic properties as the truncated variant (Dolinska et al, 2017). However, compare to full-length protein, enzymatically active melanosomal domain shows better protein expression and purification, robust laboratory handling, and should be a first choice for future drug screens.…”
Section: Commentarymentioning
confidence: 95%
“…The strategy of deleting membrane-anchoring helix is standard to simplify handling of protein. Recently, we expressed the full-length tyrosinase and demonstrated that the deletion of the anchoring helix does not affect the tyrosinase activity (Dolinska et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation